First investigation of coherent terahertz radiation at a Super Tau Charm Factory. (31st January 2022) - Gao, W.W.; Lan, J.Q.; Zhao, F.Y.; Luo, Q.
Abstract: The coherent THz radiation with long-short beam operation mode is discussed at a Super Tau Charm Factory. The beam dynamics, RF parameters and some important issues are given. Two version of short bunch length are designed. Results show that the 2.0 mm short bunch length correspond to the frequency where the radiation power decreased sharply. The short bunch length should minimized to smaller than 1.5 mm at this facility to achieve proper coherent radiation power at THz frequency region.